A study on factors affecting young adults' ability to settle in housing within the Klang Valley area - Lee, Yuen Ween (2024)
This study explores the factors affecting young adults’ ability to settle in housing within the Klang Valley area. It begins with the research background, problem statement, significance of the study, research questions, research objectives, and hypotheses of the study. Then, a comprehensive review of literature, examining Maslow’s Hierarchy of Needs, housing accommodation, home ownership, housing affordability, and various factors affecting young adults’ ability to settle in housing, such as attitudes, subjective norms, and perceived behavioural controls is presented. Drawing on relevant theories and models, a theoretical framework is proposed to guide the research.